Multi-criteria decision-making approach for optimal seismic/energy retrofitting of existing buildings. Issue 1 (February 2023) - Caruso, Martina; Pinho, Rui; Bianchi, Federica; Cavalieri, Francesco; Lemmo, Maria Teresa
Given the current climate emergency and the ambitious targets of carbon emissions reduction worldwide, retrofitting strategies on existing buildings are typically aimed at reducing their energy demand, decarbonizing the power supply, and addressing embodied carbon stored in construction materials. However, the contribution of potential earthquake-induced impacts has been traditionally not considered, while the consequences of several past events highlighted their relevant impact on the environment due to post-disaster rehabilitation activities. This study presents a multi-criteria decision-making approach for the identification of optimal renovation strategies for existing buildings, based on economic and environmental life cycle impacts (including both earthquake-induced losses and energy consumption), payback period of the retrofit investment and expected loss of life due to seismic hazard, through its application to a case-study building. Such parameters are thus suggested as meaningful decision-making variables for the choice of the best retrofitting strategy for a given building, that is the one that leads to an optimal balance between reduction of seismic vulnerability and increase of energy efficiency, based on the climatic conditions and the seismic hazard at the site of interest.